Predation, phytophagy and character state confusion among North American species of the genus Leptothrips (Thysanoptera: Phlaeothripinae) - Mound, Laurence; O’donnell, Cheryle (Zootaxa, 2017)
Difficulties are discussed of specimen preparation, of character state variation, and of species recognition in the genus Leptothrips, also the extent to which some of the species are phytophagous rather than predatory. An identification key is provided to 15 Leptothrips species from North America. Nine species described by Johansen (1987) are newly placed into synonymy, a further unrecognisable species is based on a single deformed specimen, and L. texcosensis Johansen-Naime et al. (2017) is transferred to the genus Haplothrips.